2018
DOI: 10.1186/s40643-018-0196-6
|View full text |Cite
|
Sign up to set email alerts
|

Bioleaching of copper from waste printed circuit boards by bacteria-free cultural supernatant of iron–sulfur-oxidizing bacteria

Abstract: Background:The toxicity of waste printed circuit boards (PCBs) to bacteria was considered as the major limitation in bioleaching of copper from PCBs. To reduce the toxicity of PCBs, copper extraction from PCBs was investigated using bacteria-free cultural supernatant from some metallurgical microbial consortium, whose predominant organisms were Leptospirillum ferriphilum and Sulfobacillus thermosulfidooxidans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(40 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…Although the microbial population of the mixed consortium changed under the test condition, L. ferriphilum remained the dominant bacterial species. It was sequenced for the V4 region of 16S rRNA using a high-throughput RNA sequencing technique (Wu et al, 2018). 9K medium was used.…”
Section: Materials and Bacteriamentioning
confidence: 99%
“…Although the microbial population of the mixed consortium changed under the test condition, L. ferriphilum remained the dominant bacterial species. It was sequenced for the V4 region of 16S rRNA using a high-throughput RNA sequencing technique (Wu et al, 2018). 9K medium was used.…”
Section: Materials and Bacteriamentioning
confidence: 99%
“…IOB are capable of re-oxidizing ferrous ions to ferric ions during bioleaching [20,21]. Regenerated ferric ions can be reused to oxidize sphalerite [22]. Sphalerite usually occurs in association with pyrite (FeS 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a lower leaching efficiency using the mixed cultures (mesophiles + moderate thermophiles incubated at 30°C) than that of obtained with only moderate cultures clearly indicated the suppressed activity caused by mesophiles in the mixed system. On the other hand, Wu et al 54 also employed the mixed consortia of L. ferriphilum and S. thermosulfidooxidans to successfully leach out the entire amount of copper within 2 h of leaching at 5 g L −1 pulp density. The study found indirect bioleaching as a promising option and confirmed a greater role of microorganisms in the regeneration of ferric ions as an oxidant within the system.…”
Section: Using Moderate Thermophilesmentioning
confidence: 99%